Mind–Body Intervention for Post-Surgical Breast Cancer Patients in Southern Italy: A Pilot Feasibility Study of Qigong on Patient-Reported Symptom Burden and Emotional Well-Being - Graziella Marino; Eugenia Giglio; Martina Giuseffi; Giovanni Pace; Carlo Calabrese; Marzia Sichetti; Marisabel Mecca (Cancers, 2026)
Background: Post-surgical breast cancer (BC) survivors frequently experience clusters of persistent post-treatment physical and psychological symptoms, which can negatively affect their quality of life (QoL). Mind–body interventions such as Qigong may offer potential benefit, but evidence in oncology remains limited. Methods: We conducted a single-arm pilot feasibility study at the AMICO clinic (IRCCS-CROB, Southern Italy) to evaluate the feasibility, acceptability, safety, and exploratory pre–post symptoms associated with an 8-week Qigong programme in post-surgical BC patients. Fourteen women (aged 42–73 years; stage I–III) who reported symptom burden and emotional sensitivity attended weekly one-hour classes and were encouraged to practise at home. Feasibility outcomes included adherence, completion of post-intervention assessment, adverse events, and participant acceptability. Symptom severity was assessed at baseline and post-intervention using a 0–5 study-specific symptom questionnaire score. For the secondary descriptive prevalence analysis, scores ≥ 3 were classified as indicating moderate-to-severe symptom burden. Results: All 14 participants completed the post-intervention assessment, overall intervention adherence was 92%, and no adverse events were reported. In the secondary descriptive analysis, the prevalence of moderate-to-severe pain and mood changes decreased from 64.3% to 35.7%, fatigue from 57.1% to 28.6%, anxiety from 85.7% to 42.9%, and sleep disturbances from 35.7% to 14.3%. Hot flushes decreased from 64.3% to 42.9%. Despite the heterogeneity of individual symptom trajectories, most participants reported meaningful improvements in overall well-being. Conclusions: The 8-week programme was feasible, well tolerated, and acceptable in this small real-world cohort. Symptom burden decreased during the intervention period; however, because of the uncontrolled study design and small sample size, these changes cannot be attributed specifically to Qigong. Larger controlled studies are required to estimate treatment effects and identify potential moderators of response.